2015
DOI: 10.1016/j.scog.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical (but not cognitive) recovery in schizophrenia through the experience of fictional cinema

Abstract: IntroductionOne of the criticisms of rehabilitation techniques is their limited application to the patient’s daily life. In the past, cinema has been used as a psychiatric rehabilitation tool, with the primary objective of facilitating training in social abilities and communication. In this study, we consider the use of film not only as a clinical recovery tool but also as a novel cognitive recovery tool for additional rehabilitation not only for communication and social abilities but also for all of the basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…In recent years, the use of movies from a CR-PR perspective has also been taken into account [24]. In fact, cinema is an art form that integrates, exploits, and promotes cognitive functions, since the ability to follow and understand a movie requires WM, visuospatial capacity, phonological and multisensory competency, episodic memory, mental management of time, attention, management of temporo-spatial coordinates, and social empathy with the characters [83].…”
Section: Music/movie/art Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the use of movies from a CR-PR perspective has also been taken into account [24]. In fact, cinema is an art form that integrates, exploits, and promotes cognitive functions, since the ability to follow and understand a movie requires WM, visuospatial capacity, phonological and multisensory competency, episodic memory, mental management of time, attention, management of temporo-spatial coordinates, and social empathy with the characters [83].…”
Section: Music/movie/art Interventionmentioning
confidence: 99%
“…Gelkopf et al reported benefits in SCZ psychopathology, patient state of mind, and social abilities after cinema therapy [84]. Furthermore, other groups [24] have developed structured methods based on cinema and TV series analysis [85] to induce CR benefits [86 -88].…”
Section: Music/movie/art Interventionmentioning
confidence: 99%
“…El test tiene dos versiones, una para niños (Baron-Cohen, et al, 1999) y otra para adultos (Gregory, et al, 2002); se diferencian principalmente en las situaciones contenidas en cada una de las historias, pero se mantiene la misma cantidad de estímulos. En la actualidad este test ha sido ampliamente empleado en diferentes estudios con población clínica, como en el Trastorno del Espectro Autista (Thiébaut, et al, 2016;Tin, et al, 2018;Zalla, Sav, Stopin, Ahade & Leboyer, 2009;Zalla & Korman, 2018), Trastorno por Déficit de Atención con Hiperactividad (Mary, et al, 2015;Maoz, et al, 2014), Esquizofrenia (Croca, et al, 2018;Hendriks, et al, 2016;Peña, et al, 2015), Demencias (Duclos, Desgranges, Eustache, & Laisney, 2018;Poletti, Enrici, & Adenzato, 2012) y Trastornos de la Conducta y la Personalidad (Fonagy & Bateman, 2016;Fonagy & Sharp, 2015), solo por mencionar los más frecuentes. En cuanto a su validación y adaptación transcultural, pese a ser muy utilizados principalmente en investigación, no se han realizado muchos estudios en este sentido, aunque se pueden mencionar los trabajos de Etchepare, et al (2014) en población francesa, Mehta et al, (2011) en población india, Faísca, et al, (2016) en población portuguesa y Chen et al, (2017) en población china con esquizofrenia.…”
Section: Test De Paso En Falsounclassified
“…Both diagnoses are characterized by deficits in social functioning as one of the main diagnostic criteria, especially deficits in the ability to mentalize 18 , 19 . Studies by Gürcan et al 18 , Peña et al 20 and Pino and Mazza 21 suggest that interventions using literary fiction or movies can improve clinical symptomatology in schizophrenia, as well as promote mentalizing and social functioning skills. Similarly, studies performed with people with ASD suggest that reading could improve social understanding 22 and film analysis interventions could enhance the development of perspective-taking abilities 23 .…”
Section: Introductionmentioning
confidence: 99%